Performance of pacemaker leads in alternative lead positions after tricuspid valve replacement. Issue 11 (21st October 2020) - Michaelis, Anna; Wagner, Franziska; Riede, Frank‐Thomas; Schroeter, Thomas; Daehnert, Ingo; Pfannmueller, Bettina; Gebauer, Roman Antonin; Paech, Christian
Abstract: Background: Bradycardic arrhythmias requiring pacemaker (PM) implantation are still common in patients in need of tricuspid valve replacement (TVR). Leaving an existing PM lead in an extravalvular position may represent a helpful alternative in special situations like the implantation of a mechanical TV. This study aimed to examine the short‐ to mid‐term outcome of paravalvular leads concerning lead survival and prosthesis dysfunction in patients after TVR. Methods: A retrospective case‐control study of patients with TVR and ventricular pacing was conducted. Patients from the database of the Leipzig Heart Center were included. Data of the paravalvular lead group (PVG) and coronary sinus lead group (CSG) were compared to a control group with conventional transvalvular leads (TVG). Results: Eighty patients with TVR and cardiac PM (TVG [n = 13], PVG [n = 40], and CSG [n = 27]) were included. The mean follow‐up was 2.8 years. The rate of lead revisions (TVG 15.4%, PVG 2.5%, and CSG 7.5%) was lower in PVG but without significance ( P = .286). The CSG demonstrated significantly higher pacing thresholds (1.4 V/0.8 ms) than TVG (0.5 V/0.4 ms), P = .004. However, the deterioration of threshold amplitudes during follow‐up was similar in CSG (7.4%) and PVG (7.5%) compared with controls (7.7%). Function of TV prosthesis regarding development of stenosis or regurgitation showed a similarity between the groups (regurgitation PVG P = .692, CSG P = 1; stenosis PVG P = .586, CSG P = 0.69). Conclusion: Paravalvular positioning of PM leads seems to represent a reasonable alternative to the conventional transvalvular lead positioning concerning the lead and Tricuspid Valve prosthesis's function and durability in selected patients.